Fatigue behavior and crack initiation of CAD/CAM resin composite molar crowns. Issue 10 (October 2018) - Yamaguchi, Satoshi; Kani, Renshirou; Kawakami, Kazuma; Tsuji, Manami; Inoue, Sayuri; Lee, Chunwoo; Kiba, Wakako; Imazato, Satoshi
Highlights: Fatigue behaviour of CAD/CAM resin composite molar crowns was assessed. Crack initiation of CAD/CAM resin composite molar crowns was analysed. Fracture loads of CS and KA were significantly greater than that of HC. Fracture probabilities at 120, 000 cycles of KA were the lowest. CAD/CAM resin composite crowns could be used as an alternative to ceramics. Abstract: Objective: The aim of this study was to evaluate long-term fatigue behavior using an in vitro step-stress accelerated life test (SSALT), and to determine the crack initiation point using in silico finite element analysis for computer-aided designed and manufactured (CAD/CAM) molar crowns fabricated from three commercial CAD/CAM resin composite blocks: Cerasmart (CS; GC, Tokyo, Japan), Katana Avencia Block (KA; Kuraray Noritake Dental, Niigata, Japan), and Shofu Block HC (HC; Shofu, Kyoto, Japan). Methods: Fifty-one mandibular first molar crowns luted on a resin core die were embedded in acrylic resin and covered with a polyvinyl chloride tube. Single compressive tests were performed for five crowns. SSALT was conducted for 36 crowns using three profiles and reliabilities at 120, 000 cycles, and a Weibull analysis was conducted. The maximum principal strain of each CAD/CAM resin composite crown model was analyzed by three-dimensional finite element analysis. Results: Fracture loads of CS and KA (3784 ± 144 N and 3915 ± 313 N) were significantly greater than that of HC (2767 ± 227 N) ( p < 0.05). Fracture probabilities at 120, 000 cycles were 24.6% (CS), 13.7% (KA), and 14.0% (HC). Maximum principal strain was observed around the mesiolingual cusps of CS and KA and the distobuccal cusp of HC. Significance: CAD/CAM resin composite molar crowns containing nano-fillers with a higher fraction of resin matrix exhibited higher fracture loads and greater longevity, suggesting that these crowns could be used as an alternative to ceramic crowns in terms of fatigue behavior.